Factors Associated with the Experience of Remarriage: Indonesian Family Life Survey Study - Sari Rahmaini, Indah; Valendra Granitha Shandika Puri; Mutia Afnida (Prodi Sosiologi Agama, 2024)
The article aims to look at the influence of the experience of remarriage based on age, gender, employment sector, and level of education. This research uses secondary data analysis of the Indonesian Family Life Survey (IFLS), namely book IIIA and book IV. The statistical test carried out is a regression test to seehow far is the relationship between remarriage experience and age, gender, occupation, and education using STATA software. The research results show thatFactors related to the experience of remarriage, including age, gender, employment level, and education, show that education level has the most significant decreasing impact. More specifically, individuals with higher education experience a 0.11 point decrease in the likelihood of remarrying. The p-value related to this finding is 0.0001.